Literature Review : Efek Kinesiotaping dalam Menurunkan Nyeri Punggung Bawah pada Ibu Hamil - Ida Marfu’ah (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
Introduction: Various complaints may occur during pregnancy, one of which is low back pain (low back pain). Low back pain usually occurs from the 2nd trimester and third trimester. About 45-75% of women report back pain during pregnancy. Back pain is caused by increased load at the back as a result of the total weight gained during pregnancy and fetal weight as well as hormonal changes that destabilize the spinal joints, sacroiliac joints and connective tissue. One of the interventions that can be done to reduce back pain is by using kinesiotaping. Kinesiotaping can reduce nociceptors stimution so it can suppress the pain. Method: Journal article search is done electronically using multiple databases: Sience Direct, PubMed, ProQuest and Google Scholar databases from 2010 to 2017. Results: Kinesiotaping can be used as an effective therapy to reduce lower back pain. Discussion: The use of kinesiotaping in the back area is accompanied by other complementary therapies such as pelvic tilt exercises, back exercise and breathing exercise will be more effective for lowering lower back pain. Conclusion: Kinesiotaping can be used as a complementary treatment method to reduce lower back pain in pregnancy.